La higiene postural y pausas activas en trabajadores inactivos - Chiliguana Arias, Miguel Ángel (2017)
The present research project entitled, “Postural hygiene and active pauses in inactive workers”, aims to determine the incidence of active pauses in the postural hygiene of the inactive workers of the “GAD Municipal of Riobamba”. For which the sample consisted of 16 members (men and 8 women), from 26 to 58 years old. In the research, the validated CVP35 questionnaire was used to determine professional quality life and the Nordic Kuorinka questionnaire that detects and analyzes musculoskeletal symptoms. A program of active pauses was applied in the 16 workers of the GAD Municipal Riobamba, which lasted six weeks. In the postural hygiene variable by the Kuorinka Nordic questionnaire, there were positive changes between the pre and post test, indicating that the result of the active pauses program is very significant. This allows us to relate the incidence of active pauses to the improvement of musculoskeletal pain among the 16 inactive workers, in order to improve their professional performance.